2022
DOI: 10.3390/cryst12111550
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Chitosan Nanoparticles Using of Martynia annua L. Ethanol Leaf Extract and Their Antibacterial Activity

Abstract: The herbal-based drug isolation-related research has increased recently around the globe. Accordingly, the current study was designed to evaluate the phytochemical content of ethanol extract of Martynia annua and its chitosan nanoparticles (MA-CNPs) antibacterial activity against bacterial pathogens such as Bacteroides fragilis, Streptococcus oralis MTCC 2696, Propionibacterium acnes MTCC 1951, Pseudomonas aeruginosa MTCC 424, Staphylococcus aureus MTCC 2940, E. coli MTCC 443, Bacillus cereus MTCC 441, Strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…1 B). It was reported that the UV–visible spectrum of chitosan nanoparticles ranged between 200 and 322 nm as a result of the presence of the CO group 48 . The present findings are also in agreement with those of Sathiyabama and Parthasarathy 37 , who used proteins derived from Penicillium oxalicum to produce chitosan nanoparticles with a sharp peak at 285 nm.…”
Section: Resultsmentioning
confidence: 99%
“…1 B). It was reported that the UV–visible spectrum of chitosan nanoparticles ranged between 200 and 322 nm as a result of the presence of the CO group 48 . The present findings are also in agreement with those of Sathiyabama and Parthasarathy 37 , who used proteins derived from Penicillium oxalicum to produce chitosan nanoparticles with a sharp peak at 285 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The similarity of the Rf values indicated that some of the ethyl acetate extract compounds were successfully encapsulated in the nanoparticles. Several factors affect the undetectable component with TLC including sorbent quality, humidity, plate thickness, elution distance, and ambient temperature [34]. Another factor that can exert an influence is the method of nanoparticle preparation, where some particles agglomerate and condense.…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…Research on the plants and their products or formulations used in traditional medicine has attracted a lot of interest in recent years. Indigenous cultures globally have turned to herbal remedies as a result of the resurgence of interest in medicinal plants [ 2 ]. Natural resources are becoming increasingly sought-after as a source for the creation of nutraceuticals, medications, medicines, and various cosmetics.…”
Section: Introductionmentioning
confidence: 99%